Etude de l’activité antifongique de l’extrait méthanoïque des feuilles de Salvia officinalis vis-à-vis du Verticillium dahliae agent de la verticilliose sur fève. - ELKHEDIM, Kheira; BENABED, Fatima Zahra (My University, 2023)
Natural extracts from plants could contain a variety of biologically active molecules. In this context, we attempted to evaluate the antifungal activity of methanoic extracts prepared from the leaves of Salvia officinalis, by two extraction methods; soxhlet and maceration. The results reveal a great inhibiting power of the mycelial growth of phytopathogenic fungi by the two extracts of sage with a certain preference for the extract of soxhlet. There was a direct correlation between dosage and inhibition rate.
Keywords: Vicia fabae; Verticillium dahliae; extracts; Salvia officinalis; antifungal